Common Institutional Ownership and Auditor Risk Response - Cheng, Cheng (Transactions on Economics, Business and Management Research, 2024)
Based on the data of China's Shanghai and Shenzhen A-share listed companies from 2010 to 2021, this paper investigates the relationship between a company's common institutional ownership and auditors' risk response behavior. The study shows that common institutional ownership drives auditors to increase audit investment and audit fees, which supports the collusive fraud effect. Further analysis reveals that the effect of common institutional ownership on auditor risk response behavior is more pronounced in firms with a higher degree of industry competition as well as in state-owned enterprises, and that Big Four auditors will be more sensitive to the collusive fraud effect of common institutional ownership and respond to this risk mainly by increasing audit investment. This paper not only enriches the research literature on the factors influencing auditors' risk response behavior and the economic consequences of common institutional ownership but also sheds light on how to improve corporate governance and regulate the market order in practice.